Access to water in the context of the international watercourse: A theory of the community of interest - Vučić Mihajlo (Anali Pravnog Fakulteta u Beogradu)
Securing free and equal access to water for individuals is foremost an objective of international water law. This article analyses the community of interest theoretical framework for the creation and implementation of rules that can achieve this objective. This theory is in line with the natural unity of the watercourse that traverses political borders between states. However, legal doctrine is not unanimous concerning its practical value, state practices largely evade it, and case law only provides declarative support without indicating precise contents of community rights and obligations. It seems that practical application of the community of interest theory is only possible through meticulous and systematic application of positive legal rules based on limited territorial sovereignty theory, in the spirit of joint management and use of common water resources.